Development and Evaluation of an in ovo Plasmid DNA Vaccine Against Infectious Bursal Disease Virus - Moura, L.; Liu, M.; Vakharia, V.N. (International Journal of Poultry Science, 2007)
Infectious Bursal Disease Virus (IBDV) is a highly contagious disease of chickens, which is controlled by live and inactivated vaccines. In this study, we evaluated a novel approach to vaccinate chickens against IBDV using DNA vaccinology. Plasmid DNA was administered in ovo to 18-day-old embryos. The DNA vaccine expresses the polyprotein VP2-VP4-VP3 of IBDV. The VP2 gene expresses epitopes of D78 strain and variant strain of GLS. VP3 and VP4 genes are from D78. VP2-VP4-VP3 genes were inserted into a plasmid vector (pVAX1) and their expression verified by immunostaining assays. SPF and fertile broiler eggs with maternal antibodies were vaccinated and hatched chicks were challenged against IBDV-STC. Each embryo received 60 µg of the DNA vaccine delivered into the amniotic cavity. In addition, a control group was inoculated with plasmid DNA without insert. Two groups of birds (SPF and broilers) received a booster immunization with baculovirus expressed-proteins of IBDV. The DNA vaccine had no detrimental effect on hatchability or first week post-hatch survival. In ovo vaccination generated detectable humoral immune responses as measured by ELISA. Antibody response was significantly enhanced two weeks after the birds received the IBDV-protein boost. However, no significant protection was observed in all vaccinated groups. BF had severe microscopic lesions. Broilers vaccinated with plasmid DNA or IBDV-protein had partial protection possibly due to maternal antibodies.